Analisis Pengukuran Zakat Menggunakan Indeks Zakat Nasional (IZN) 2.0 (Studi: BAZNAS Kabupaten Lima Puluh Kota) - Nur Aziah; Rika Wedia Nita (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the impact of zakat management using the National Zakat Index (IZN) 2.0 at BAZNAS Lima Puluh Kota Regency. IZN was introduced in 2016 as a standard measurement tool to evaluate the performance of national zakat management in Indonesia. The study used a qualitative method with a literature study approach and field research. Data were obtained through interviews with zakat leaders and amil, observations, and documentation related to zakat collection and management practices. Analysis was conducted by filling out the IZN form provided by the Baznas center and comparing it with indicators in the NZI book. The results showed that the National Zakat Index value of Baznas Lima Puluh Kota Regency reached a score of 0.74 and is in the good category. This value exceeds the standard score of 0.60 which is included in the very good category. This achievement indicates that zakat management at Baznas Lima Puluh Kota Regency is running effectively and places it among the top three best Baznas in West Sumatra.